INTRODUCTION TO BIOMEDICAL ENGINEERING: RESEARCH PROJECTS & CASE STUDIES - Muhammad Mahadi Abdul Jamil (Penerbit UTHM, 2015)
This book aimed to provide a significant reference medium for undergraduate students whom wish to precede their final year projects towards a research based study. The example studies included will be useful and further assist the students to trigger their own idea according to the research method presented extensively in six chapters. The postgraduate students will also benefit from this research book where the main idea of commencing a research project are shown in various example studies that would give a flow for the students on where to start their own projects. The studies presented here consist of product design & development, modelling & simulation, review, quantitative analysis and also image processing. These combinations will allow the research students to gain a prior knowledge on the type of studies that they would like to embark on. By having the selected six chapters presented here will answer many other questions of the students on conducting their research. Thus, at the same time this book will be a useful reference book for both undergraduate and postgraduate levels.